Law in The Era of Digitalization and Covid-19 Pandemic - Dara Puspita Riyawan; Jennifer Clarence; M Raihan S lexmana (Veteran Law Review, 2023)
Legal developments in Indonesia have an impact on changes in various aspects of the law, such as changes in the form of settlement in the judiciary. Some judicial institutions have indeed implemented a modernization process, but not a few judicial institutions have still used the same litigation method for decades. In the midst of the Covid-19 pandemic, some parts of the justice system experienced an increase in workload, while other parts experienced a decline where there was an increase in requests in the criminal justice sector to consider the repatriation of prisoners in order to reduce the population in prisons. The method used in making the paper entitled "Law in the Era of Digitalization and the Covid-19 Pandemic" is the historical method. This method relies on four activity steps, namely: Data collection (Heuristics), Source criticism (Verification), Interpretation (Interpretation), and Historical Writing (Historyography). The purpose of this journal's research method is to find out the development and application of lawin the digitalization era and after the Covid-19 pandemic. The result of the conclusion of this method is that the Covid-19 pandemic cannot prevent the fairest enforcement of laws. In this digitalization era, remote trials can still be carried out despite the Covid-19 pandemic. In this era of digitalization, it is easier to implement legal processes in Indonesia.